Batik Fashion Trends and National Identity - Vidyana Yulianingrum; Sri Ranita; Lintang Sabrang Kinasih Basuki; Atara Loveana Wijaya; Moses Glorino Rumambo Pandin (Faculty of Economics, Law, and Humanities, 2022)
National identity is an identity that distinguishes one nation from another. The rapid development of globalization in the digital era has been able to influence national identity and has the potential to undermine the nation's cultural values. One example is the change in the function of fashion from what was originally only a primary need, now it has doubled as a lifestyle and trend of people in the world. However, the fashion trend in Indonesia is dominated by the influence of foreign cultures. Fashion from western countries and Korea has become the daily consumption of Indonesian people. Therefore, the acculturation of Indonesian culture with current fashion trends needs to be done so as not to further fade the nation's national identity. Batik as an intangible cultural heritage can also become the national identity of the Indonesian nation. So, researchers took the initiative to acculturate batik with current fashion trends in an effort to strengthen the national identity of the Indonesian nation. Knowing the interest of the younger generation, regarding our innovation in the form of acculturating batik with fashion trends. Survey-based research method by providing open-ended questions related to respondents' interest in acculturating batik with contemporary fashion trends to the population of the young group aged 15-19 years through an online survey with 100 samples and 9 samples for interviews with the surrounding distribution area around the islands of Borneo and Java. The younger generation is proud when wearing batik, but they don’t have the habit of using batik in their daily life. Researchers offer acculturation innovations to all respondents and they are interested in our innovations because they can still follow fashion trends in addition to wearing batik as their daily clothes and can give the effort to strengthen their national identity.